ADAPTATION OF NATIONAL ECONOMIC LAW TO INTERNATIONAL INTEGRATION AND DIGITAL TRANSFORMATION: A LITERATURE REVIEW - Gunawan Widjaja (Adisam Publisher, 2025)
This study examines the adjustment of Indonesia's national economic law in facing two major phenomena, namely international integration and digital transformation, through a literature review method. Economic globalisation requires regulatory harmonisation so that Indonesia can actively participate in international trade and investment without sacrificing national interests. Meanwhile, the rapid development of digital technology has changed the economic paradigm and created a need for regulations that are responsive to innovation and personal data protection. This literature review identifies the challenges, opportunities, and legal adjustment strategies that must be undertaken to maintain a balance between domestic interests and global demands, while creating an inclusive and sustainable digital economic ecosystem. The results of this study are expected to serve as a reference for policymakers and academics in developing adaptive and progressive economic legal regulations.